Fostering Student Success: A Prevailing Provision for Dyscalculia and Dyslexia in the School Curriculum and Strategies for Support - Kunwar, Rajendra (Nepal Journal of Neuroscience, 2024)
This article examines the impact of dyscalculia and dyslexia on students’ mathematics learning and proposes strategies for supporting learners with these learning disabilities. It provides a concise overview of dyscalculia and dyslexia, emphasizing their distinct characteristics and prevalence rates within the Nepalese context. The study explores the challenges faced by students with dyscalculia and dyslexia in mathematics education and discusses the importance of inclusive education. It also provides an overview of the school-level curriculum in Nepal, highlighting the effects of dyscalculia and dyslexia on mathematics learning and the specific challenges experienced by students with these disabilities. The article uncovers areas within the school-level curriculum in Nepal that require attention and offers practical ways to support learners with dyscalculia and dyslexia. Overall, this article provides valuable insights into the challenges faced by students with dyscalculia and dyslexia in learning mathematics and offers practical recommendations for developing an inclusive curriculum that caters to the specific needs of the dyscalculic and dyslexic learners.